Pengembangan Strategi Usaha Melalui Metode Competitive Positioning Analysis Pada CV. Dina Garmen Jakarta (Studi Kasus Pada Produk Baju Koko Raihan Moslem Wear) - Muhammad Raihan; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2018)
Garment is one of the biggest contribution in the development of the textile industry today. Garment or apparel is one of the keys to increasing donations in the textile sector, an industry that is one of Indonesia's mainstay sectors in the context of national economic growth. One of the Muslim clothing products in the city of Jakarta is Raihan Moslem Wear developed by CV. Garment Dina. Raihan Moslem Wear is one of the leading Muslim clothing brand specialists for koko or Muslim men's clothing products in Indonesia. Raihan Moslem Wear was first created in 1996. This study aims to find out what strategies are appropriate for CV. Garment Dina. The sample in this study were the owners, staff and 25 consumers of CV. Garment Dina. This study uses descriptive qualitative research. The research design was used by using purposive sampling method. Data collection is done using questionnaires and interviews. The results and discussion show the direction of the strategy on the CV. Dina Garment is making distributor agents, developing product variants, expanding markets, innovating marketing, producing other products and maintaining quality but by maintaining price stability. The suggestion that can be conveyed is that the company can maintain the company's unique motives and maintain product quality, and it is expected that the company can become a trend initiator so as not only to become a follower of the trend but to become the trend maker itself. In addition, CV. The Garment Dina is expected to be able to do an effective and efficient promotion or advertisement even though it costs money because it is very important for the company to increase awareness for the company.